Cardiac organoids: a new tool for disease modeling and drug screening applications - Yaqinuddin, Ahmed; Jabri, Abdullah; Mhannayeh, Abdulaziz; Taftafa, Bader; Alsharif, Mohamed; Abbad, Tasnim; Khan, Jibran; Elsalti, Abdulrahman; Chinnappan, Raja; Alshehri, Eman A.; Alzhrani, Alaa; Obeid, Dalia A.; et al. (Frontiers in Cardiovascular Medicine, 2025)
Cardiac organoid is a miniature and simplified three-dimensional (3D) cellular model system grown from progenitor cells or stem cells that more accurately mimic the significant biological characteristics and functions of the normal cardiac system than conventional two-dimensional (2D) models. With continued advances in 3D culture approaches, the cardiac organoid models produced through self-organization strategy following developmental induction conditions exhibit higher metabolic similarities and physiological relevance. Increasing evidence demonstrates that cardiac organoids based on the in vitro model system are useful platforms for studying human cardiac biology and pathophysiology. Despite significant advancements, the development of cardiac organoids has not progressed as far as other types of organoids due to the intricate cellular structure and microenvironment of the heart. In this review, we highlight the current classification and bioengineering strategies for establishing cardiac organoids using Matrigel and decellularized extracellular matrix derived culture platforms followed by a review of contemporary reports of their use in development biology, disease modeling, drug testing and efficacy evaluation. We also shed the light in the current limitations and future perspective of the cardiac organoid to motivate future research and accelerate the widespread adoption of organoids platforms.